Pendampingan Pembelajaran Tajwid Dan Makharijul Huruf Sebagai Upaya Meningkatkan Kemampuan Membaca Al-Quran Yang Baik Dan Benar Pada Santri Tpa Darul Anwar Desa Keeh Kecamatan Meurah Mulia - Maulina, Isra; Sufrizal, Sufrizal; Zefri Maulana (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2024)
Learning tajweed and makhrijul huruf is an important thing for Muslims to be able to read and understand the Al-Quran properly and correctly with matters related to studying the Al-Quran. Darul Anwar TPA is thesubject of one of the community service lecture activities. Based on observations in the field, many Keeh Village TPA students have been able to read the Quran, but the use of tajweed and makharijul letters is still not correct. The objectives in the implementation of learning tajweed and makhrajul letters are: 1). To reduce the possibility of reading the Quran incorrectly, which can change its meaning; 2). to help understand the Quran accurately and completely. The implementation method in this community service activity is PAR (Participatory Action Research) which is supported by observation, interviews and lectures. The results of this community service show that 65% of the students have been able to apply the science of tajweed to be able to read the Quran properly and in accordance with the rules of tajweed science and 80% of the students of TPA Darul Anwar Keeh Village are able to place or pronounce hijaiyah letters according to makhraj. The application of this mentoring method is very helpful for effective learning in educating children to be more active in learning and understanding tajweed and makharijul letters.